Consumption Pattern Counseling About “Anti Hypertension and Anti Diabetes” and Exercise for the Elderly to Avoid Hypertension in Tenaru Village - Rahmawati, Arsya; Madani, Anan; Rohmawati, Karima (UNUSA Press, 2024)
The aging process as an accumulation of damage at the cellular and molecular levels that occurs over a long period of time is often associated with the occurrence of noncommunicable diseases. Various studies have shown that age is one of the risk factors for non-communicable diseases, such as those often experienced by the elderly, namely hypertension and diabetes. Implementation methodhealth promotion to the community, especially vulnerable communities such as the elderly through blood pressure checks and Random Blood Sugar (GDA) tests and also providing counseling on consumption patterns about